Between the hand and the head: How things get done, and how in doing the ways of doing are discovered. Issue 2 (3rd June 2014) - Gherardi, Silvia; Perrotta, Manuela
Abstract : Purpose: – The purpose of this paper is to add a new term to the vocabulary of practice-based studies: "formativeness", which denotes the kind of knowledge that is generated in the process of realizing the object of the practice and that is discovered while the form of the object is being shaped. This term focuses the analysis on how the elements of a practice are held together, rather than on what elements are involved in a practice. Design/methodology/approach: – Inspired by grounded theory, an empirical research study on craftswomen and their practical creativity (between the hand and the head) was designed. Storytelling was used in order to elicit the verbalization of the craftswomen's ways of knowing/doing, and the episodic interview was the technique employed to access and present the data. Findings: – Formativeness can be described and interpreted as the effect of the following dimensions: the emergence of the object, the golden rule of realization, forming by hybridization, experimentation, playfulness, attachment to matter, and proper realization. Originality/value: – The study's contribution may be evaluated in relation to how a vocabulary for describing and interpreting knowing-in-practice is constructed. Formativeness makes it possible to name the process by which ways of doing are discovered while activities are being performed. It contributes to a critique of representational knowledge, while offering an alternative line of inquiry.